1991
DOI: 10.1104/pp.96.1.331
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Does Not Compete with Calcium in Saturating Plasma Membrane Sites Regulating 22Na Influx in Salinized Maize Roots

Abstract: Half maximal inhibition of sodium ('Na ) influx into maize (Zea mays L.) root segments incubated in solutions containing from 0.25 to 100 millimolar NaCI was consistently attained with external calcium activity at 0.26 ± 0.10 millimolar. Sodium ions do not appear to compete with calcium during initial binding to sites on the plasma membrane that participate in the regulation of sodium influx under saline conditions.Increasing the activity of calcium ions in the saline root media of glycophytic crop plants can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 15 publications
(37 reference statements)
1
21
1
Order By: Relevance
“…Increasing the external concentration of calcium largely counteracted this displacement (Lynch et al, 1987;Lynch and La Èuchli, 1988). Maize has proved to be a suitable test plant for investigating the effects of salinity on the whole plant, as well as on the organ and cellular levels of organisation, and for defining plant response to the competitive interactions between Na and Ca 2 (Zidan et al, 1991). In high Na /Ca 2 substrates, maize is particularly sensitive to growth inhibition and exhibits significant changes in morphology and anatomy (Maas and Grieve, 1987;Evlagon et al, 1990;Cramer, 1992).…”
Section: Effects Of Salinity On Calcium-related Disorders In Reproducmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the external concentration of calcium largely counteracted this displacement (Lynch et al, 1987;Lynch and La Èuchli, 1988). Maize has proved to be a suitable test plant for investigating the effects of salinity on the whole plant, as well as on the organ and cellular levels of organisation, and for defining plant response to the competitive interactions between Na and Ca 2 (Zidan et al, 1991). In high Na /Ca 2 substrates, maize is particularly sensitive to growth inhibition and exhibits significant changes in morphology and anatomy (Maas and Grieve, 1987;Evlagon et al, 1990;Cramer, 1992).…”
Section: Effects Of Salinity On Calcium-related Disorders In Reproducmentioning
confidence: 99%
“…In high Na /Ca 2 substrates, maize is particularly sensitive to growth inhibition and exhibits significant changes in morphology and anatomy (Maas and Grieve, 1987;Evlagon et al, 1990;Cramer, 1992). Inhibition of maize root cell production and elongation appear to underlie the regulation of root growth by NaCl-salinity and these processes may be partially restored by addition of substrate-calcium (Cramer et al, 1988;Zidan et al, 1991). Water transport properties of maize primary roots are adversely affected by NaCl-induced morphological and anatomical changes (Evlagon et al, 1990;Neumann et al, 1994).…”
Section: Effects Of Salinity On Calcium-related Disorders In Reproducmentioning
confidence: 99%
“…The fact that raising the calcium concentration (and activity) in dilute nutrient solutions used for hydroponic culture of salinized plants can increase root (and leaf) growth, is well established (e.g. Lehaye and Epstein, 1969;Maas and Grieve, 1987;Zidan et al, 1991). Salinity induced changes in root length, mature cell length and root diameter could be caused by a) toxic effects of salt on the metabolism of expanding cells and diameter are means, ±SD, n = 10 after4d growth in aerated nutrient solutions (NS) ± 100 mol JIl-3 NaCI ± 10 mol m-3 CaCI2 (Adapted from Evlagon et al, 1990).…”
Section: Growth Responses To Salinitymentioning
confidence: 99%
“…Calcium addition to a medium alleviates salt stress symptoms in many species (Maathuis and Amtmann 1999). In salt-affected plants, Ca 2+ supply restored root elongation (Zidan et al 1990) and shoot growth (Yeo 1998) and reduced total Na + accumulation (Cramer et al 1989;Zidan et al 1991). We previously found that growth inhibition in salt-treated Arabidopsis plants could be attributed to the limitations in K + , Ca 2+ and/or N supply to the leaf (Attia et al 2008).…”
Section: Introductionmentioning
confidence: 99%